"Advocacy cheating": teacher noncompliance in standardised literacy testing. Issue 3 (14th August 2018) - Johnson, Lauren
Abstract : Purpose: The purpose of this paper is to explore teachers' noncompliance with secondary-level standardised literacy testing in Tasmania, Australia, particularly their motivations, behaviours and justifications. This paper challenges pervasive views regarding test noncompliance, suggesting a reframing as "advocacy cheating": noncompliance for purposes of advocating for and supporting students. Design/methodology/approach: The research used a single case study design, with a simple thematic analysis of the qualitative data. The design enabled data to be collected during one iteration of the examined test regime, with depth of exploration into participants' experiences and perspectives. Findings: Findings indicate that small number of participants were engaged in test rule noncompliance at all stages of the testing regime: before, during and following the tests. This paper presents the concept of "advocacy cheating", illustrated in these data through the motivations presented by participants for their noncompliant actions and the forms of noncompliance used. Research limitations/implications: The small sample size and single site problematise drawing much broader comparisons. The age of the data means that current test processes and requirements have developed. Larger-scale studies might enable identification of ways in which this current regime has and might be improved. Practical implications: This study's findings and its focus on the classroom and teacher experience of testing provide insights into a widely debated and publicly important phenomenon. Originality/value: The concept of "advocacy cheating" provides a newer way of considering and interpreting the range of ways in which teachers implement standardised tests.